Three-year Randomized Prospective Clinical Trial of Class II Restorations Using Flowable Bulk-fill Resin Composites - Moda, M. D. [UNESP]; Briso, André Luiz Fraga [UNESP]; Hoshino, Iae [UNESP]; Frascino, Smb [UNESP]; Santos, Paulo Henrique dos [UNESP]; Gonçalves, D. M. [UNESP]; Fagundes, Ticiane Cestari [UNESP] (Operative Dentistry, 2021)
OBJECTIVES: This randomized, prospective, and split-mouth study aimed to evaluate flowable bulk-fill resin composites in class II restorations and to compare with a conventional layering technique after a 3-year follow-up. METHODS AND MATERIALS: Fifty-three subjects received three class II restorations according to the restorative systems: conventional microhybrid resin composite (PA, Peak Universal + Amelogen Plus, Ultradent), flowable bulk-fill and nanoparticulate resin composites (ABF, Adper Single Bond 2 + Filtek Bulk Fill Flow + Filtek Z350XT, 3M Oral Care), and flowable bulk-fill and microhybrid resin composites (XST, XP Bond + SDR + TPH3, Dentsply). The clinical performance and interproximal contacts were evaluated. Statistical analyses were performed using the equality test of two proportions, Logistic regression analysis, Friedman, Wilcoxon, Kruskal-Wallis, and Mann-Whitney tests (a=0.05). RESULTS: Forty-seven patients were evaluated at 3 years. XST bulk-fill restorative system presented higher marginal discoloration than PA, and the opposite occurred for surface staining. All restorative systems resulted in decreased interproximal contacts, occurring early for XST. CONCLUSIONS: Although the restorative system using incremental technique presented better performance for marginal discoloration, one of the restorative systems that used flowable bulk-fill resin composite (XST) showed the lowest surface staining. All restorative systems had decreased proximal contact over time.